Osteoblasts sense extracellular levels of phosphate to control the local expression of phosphatases for matrix mineralisation - Soher Nagi Jayash; Thomas Duff; Qaisar Tanveer; Worachet Promruk; Colin Farquharson (Bone Reports, 2025)
The provision of inorganic phosphate (Pi) for biomineralisation is under systemic and local control. Locally, osteoblast production of phosphatases such as tissue-nonspecific alkaline phosphatase (TNAP) and PHOSPHO1 is required for normal skeletal mineralisation and osteoblasts may sense extracellular Pi concentrations to control local phosphatase activity and thereby “fine-tune” Pi production and delivery for biomineralisation. This has been poorly explored and this study examined the ability of osteoblasts to sense and respond to extracellular Pi to control the local expression of TNAP and PHOSPHO1.Extracellular Pi downregulated the expression of PHOSPHO1 and TNAP by human primary osteoblasts at both mRNA and protein levels. Increasing Pi concentrations also reduced the mRNA expression of the type III Na- Pi co-transporters, PiT-1 and PiT-2 and selectively enhanced ERK1/2 phosphorylation. Inhibition of PiT-1 and PiT-2 by Foscarnet or MEK1/2 by UO126 abolished the downregulation of PHOSPHO1 and ALPL expression by extracellular Pi. Moreover, extracellular Pi phosphorylated fibroblast growth factor receptor (FGFR) substrate 2α (FRS2α) and this activation was abolished by Foscarnet. Also, blocking FGFR signalling inhibited the phosphorylation of ERK1/2 and prevented the decrease in ALPL and PHOSPHO1 expression by extracellular Pi. Similar results were observed in cultured murine calvaria. Osteoblast matrix mineralisation by extracellular Pi was dependent upon type III Na- Pi co-transporters and FGFR signalling.In conclusion, these results suggest an interplay between FGFR and Pi transporters is required for osteoblasts to sense and respond to extracellular Pi. This understanding advances our knowledge of the molecular control of physiological bone mineralisation by osteoblasts.